Responsiveness of Daytime Sleepiness and Fatigue Scales in Myotonic Dystrophy Type 1. (20th March 2022) - Laberge, Luc; Gallais, Benjamin; Auclair, Julie; Dauvilliers, Yves; Côté, Isabelle; Mathieu, Jean; Gagnon, Cynthia
ABSTRACT: Daytime sleepiness and fatigue are prominent symptoms of myotonic dystrophy type 1 (DM1) that can be amenable to treatment in the context of randomized controlled trials. No study has yet documented whether self-reported measures of daytime sleepiness and fatigue can detect change over time and the meaning of this change. The aim was to explore indicators of responsiveness to change and interpretability for the Daytime Sleepiness Scale and the Fatigue Severity Scale in 115 DM1 prospectively followed patients. Results suggest that these two self-reported questionnaires are sufficiently sensitive to detect changes beyond expected measurement error over time in this population.